A serological survey on cryptosporidiosis in Najran region, Southwestern Saudi Arabia with reference to some epidemiological features of the infection - Elshahawy, Ismail (International Journal of Advances in Medicine, 2017)
Background: Cryptosporidium infection remains a major public health issue, but its epidemiology in humans is still unclear, particularly in Southwestern Saudi Arabia. Hence, this study was designed to determine the infection status of Cryptosporidium and the reservoir hosts in southwestern Saudi Arabia community and to recognize the associated risk factors, with evaluating the diagnostic performance of the techniques used. Methods: A total of 576 stool specimens and sera were screened for cryptosporidiosis using modified Ziehl neelsen technique and a newly developed enzyme-linked immunosorbent assay (ELISA) respectively, between September 2015 and December 2016. Results: Of the 576 samples assayed, 9.5 and 20.8% were positive for Cryptosporidium oocyst and anti-Cryptosporidium antibody, respectively. The seropositivity was positively correlated with age, especially in the age group less than 6 years old. Likewise, the prevalence of Cryptosporidium infections in males was significantly higher than in female counterparts (P < 0.05). The current study revealed that the maximum number of cases, 22.4%, was observed during the months of January to April, indicating marked significant seasonal variation. Sensitivity and specificity of newly developed Elisa technique when compared to acid-fast were 100% and 88.24%, respectively. Conclusions: This is the first study highlighting that Cryptosporidium infections are still an important public health problem in Southwestern Saudi Arabia. Therefore, health education would be the best way to prevent the infections and the serological assays proved to be useful mean to provide more accurate information regarding community levels of Cryptosporidium infection.